Kajian Desain Awal: Identifikasi Kebutuhan Pengguna dan Penentuan Target Spesifikasi Produk Modul Konversi Kit Sepeda Motor Listrik - Patrisius Edi Prasetyo; Mars Sailentdra; M. Fahrudin Al Fadli (Fakultas Seni Rupa dan Desain ITB, 2023)
The urgency of this research is that Indonesian people still have low interest in using electric motorbikes, indicating that sales of electric motorbikes in Indonesia are still low. Indonesian people are skeptical about electric motorbikes due to their battery life and the relatively higher price than conventional motorbikes. In this research, an additional EM module product was designed as a solution to answer these doubts. This research is an initial design process aimed at obtaining target product specifications for additional EM modules from the results of identifying user needs as a basis for the subsequent design process. The additional EM module product applies an EM conversion system that is installed on the ICEM product without losing its original ability to use a gasoline energy source, thereby minimizing procurement costs using electric motor technology on conventional motorbikes and without worrying about running out of battery when in use. This research uses the front-end activity design method to design additional EM module products and produces 30 customer needs with percentage levels of importance and 24 product specification target metrics in marginal and ideal values to be used as abasis for the subsequent design process.